Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/09548963.2013.817652
|View full text |Cite
|
Sign up to set email alerts
|

How US cultural districts reshape neighbourhoods

Abstract: Cultural districts are an increasingly popular and important element of both urban and cultural experiences in the United States. Cultural districts get invoked as a tool for revitalising neighbourhoods and regions, cultivating arts and cultural resources, and other goals. This article briefly describes the phenomenon of cultural districts in the United States, reviews some claims made about their impacts, and provides evidence of districts' effects. Neighourhood-level statistical analyses identify socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 8 publications
(14 reference statements)
6
29
1
Order By: Relevance
“…Much work remains to be done to understand how diversity and artists influence perceptions of neighborhood character and how they further affect neighborhood revitalization (Noonan 2013). Research has shown that nonprofit organizations and amenities like coffee shops that are associated with artist concentration contribute to lower crime levels (Papachristos et al 2011;Sharkey et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Much work remains to be done to understand how diversity and artists influence perceptions of neighborhood character and how they further affect neighborhood revitalization (Noonan 2013). Research has shown that nonprofit organizations and amenities like coffee shops that are associated with artist concentration contribute to lower crime levels (Papachristos et al 2011;Sharkey et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is almost universally understood as a promotional tactic for the neighborhood rather than having any tangible benefits, such as a promised tax-break for homeowners or artists selling artwork (See McGough and Messino, 2010, for an assessment of the financial benefits of A&E Districts in Baltimore). This is not surprising, as much previous research has discussed the role of branding and themed environments in urban revitalization and consumer-driven placemaking (Zukin, 1995;Gottdiener, 1997;Scott, 2000;Evans, 2003;Currid, 2009;Noonan, 2013). One of the early organizers of Baltimore A&E Districts plainly told us:…”
Section: The Aande District: 'Branding Versus Benefits'mentioning
confidence: 88%
“…Where the arts grow, findings suggest that in the US they generally improve housing values Noonan, 2013;Stern & Seifert, 2010;Woronkowicz, 2016) and income Noonan, 2013;Schuetz, 2014;Woronkowicz, 2016) in urban and nationwide contexts. In Canada, however, Silver and Miller (2013) find that arts relations to income depend both on the type of arts that grow and type and strength of the cultural scene.…”
Section: Comparative Modellingmentioning
confidence: 99%